METODE PENDUGAAN KEMAMPUAN SUPPLY PRODUK KAYU DARI BERBAGAI INDUSTRI DI PROPINSI RIAU - Han Roliadi; Buharman Buharman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The aim of this investigation is to create a prediction model on the potentiality of supplying merchant wood products. The investigation was carried out in the province of Riau Four Sawmills and two plywood industries were selected for this study.The annual data concerning production factors (input factors) such as material input (x1), the price of raw material (x2), The cost of additive matters/auxiliaries (x3), the designed production capacities (x4), and the price per unit product (x5) were collected. In addition, their annual production (Y) was also recorded.The prediction model is intended to interpret the relationship between production factors and their actual production per annum by applying multiple regression analysis. The prediction models for Sawmill products and plywood products are presented respectively as follow :Y = 7.2140 + 0.5717 x1 – 0.1323 x2 – 0.1787 x3 + 0.0078 x4 + 0.2188 x5, andY = 10.1774 + 2.1724 x1 – 0.6431 x2 + 0.0071 x3 + 0.6182 x4 + 0.7128 x5.Both models show a considerable high of confidence (P = 0.95).